2016
DOI: 10.1515/geo-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and optimization of multi-lateral wells using MODFLOW unstructured grids

Abstract: Multi-lateral wells have been increasingly used in recent years by different industries including oil-and gas industry along with coal bed methane-and water production. The common purpose of these wells is to achieve a higher production rate per well. More and more sophisticated well patterns and geometries can be implemented in practice which calls for improved modelling techniques. Complicated well geometries and small lateral diameters require high resolution models in the vicinity of the wells. With struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…and discipline-vise to hydrology, Lux et al were able to simplify the optimization of multi-lateral well patterns using unstructured grids, while keeping a similar effectiveness as the ones in literature [13].…”
Section: Papers Presentedmentioning
confidence: 99%
See 1 more Smart Citation
“…and discipline-vise to hydrology, Lux et al were able to simplify the optimization of multi-lateral well patterns using unstructured grids, while keeping a similar effectiveness as the ones in literature [13].…”
Section: Papers Presentedmentioning
confidence: 99%
“…The papers in this in this special issue of Open Geosciences were selected from within the framework of this conference with the hope of providing insights into-, and bridging the gap between mathematical and statistical practice among case studies from classical environmental applications of multivariate statistics [8,9] through the solution of reservoir geological problems [10][11][12][13][14], to the application of methods that are new to this field of science [15] along with many other aspects of geology and environmental sciences. The issue consists of two main parts, the first part deals with studies mainly concerning petrology, while the second is related to urban/classical environmental problems, handled using geostatistics.…”
Section: Papers Presentedmentioning
confidence: 99%
“…In present workbuilding on the advantages demonstrated previously (Lux et al, 2016) we applied unstructured grids (USG) to model multilateral wells using the MODFLOW-USG code that simulates groundwater flow using a generalized control volume finite-difference approach, which allows grids other than orthogonal structured grids (SG) (Panday et al, 2013).…”
Section: Unstructured Gridmentioning
confidence: 99%
“…In a previous paper (Lux et al, 2016) it has been demonstrated that unstructured grids are more efficient in modelling multilateral wells than structured grids from a computational point of view while also providing better resolution. That paper also investigated optimal geometries for radially distributed and fishbone type multilateral wells in a homogenous, isotropic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Sbai [28] evaluated the improvement of the performance of using USG to represent the aquifer heterogeneity and compared it with the homogeneous coarser grid model. Lux [29] analyzed the difference between using the structured grid and the unstructured grid to simulate the multi-lateral wells. The unstructured grid could provide higher resolution keeping cell numbers relatively low by only refining around the wells.…”
Section: Introductionmentioning
confidence: 99%